2014
DOI: 10.1007/s13277-014-2714-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of CYBA (p22phox) and catalase genetic polymorphisms and their possible epistatic interaction in cervical cancer

Abstract: Human papillomavirus (HPV) infection is necessary but not a sufficient cause for the development of invasive cervical cancer (ICC). Epithelial tissues, target for HPV, are exposed to reactive oxygen species (ROS) associated with tumor initiation and progression. The NADPH oxidase (NOX) and catalase (CAT) are involved in hydrogen peroxide (H2O2) production and inactivation, respectively. P22phox is the NOX subunit encoded by the CYBA gene that has a functional polymorphism (C-242T). This protein is involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…In a case-control study, we observed a greater risk for developing ICC associated with the homozygote genotype TT of CAT polymorphism C-262 T polymorphism of the CAT gene (OR = 3.03, 95% CI 1.46-6.29, P = 0.003) [31]. Similarly to other cancers types, the T variant of this polymorphism is associated to a decreased enzyme activity, generating high levels of ROS [32][33][34].…”
Section: Catalasementioning
confidence: 77%
See 1 more Smart Citation
“…In a case-control study, we observed a greater risk for developing ICC associated with the homozygote genotype TT of CAT polymorphism C-262 T polymorphism of the CAT gene (OR = 3.03, 95% CI 1.46-6.29, P = 0.003) [31]. Similarly to other cancers types, the T variant of this polymorphism is associated to a decreased enzyme activity, generating high levels of ROS [32][33][34].…”
Section: Catalasementioning
confidence: 77%
“…Similarly to other cancers types, the T variant of this polymorphism is associated to a decreased enzyme activity, generating high levels of ROS [32][33][34]. The interaction of CC genotype of p22phox polymorphism and the TT genotype of CAT leads to a higher risk for ICC (OR = 3.95, 95% CI 1.07-14.52, P = 0.032) [31].…”
Section: Catalasementioning
confidence: 99%
“…The association between the polymorphism of the CAT C262T gene and increased skin cancer risk was also confirmed30 (CT + TTvs CC: OR = 1.19, 95%CI = 1.00–1.41, P = 0.04; CT vs CC: OR = 1.21,95%CI = 1.02–1.44, P = 0.03). Meanwhile, the CAT C262T polymorphism retained its high position for predicting the susceptibility to cervical cancer12 (TT vs CT + CC: OR = 2.85, 95%CI = 1.44–5.65, P = 0.003; TT vs CC: OR = 2.88, 95%CI = 1.41–5.87, P= 0.004; T vs C: OR = 1.96, 95%CI = 1.31–2.93, P = 0.001). However, no evidence of statistical significance could be detected in other cancer types.…”
Section: Resultsmentioning
confidence: 99%
“…The CAT gene, which is located on chromosome11p13, consists of 12 introns and 13 exons10. There are several single nucleotide polymorphisms (SNPs) identified in the CAT gene, of which the rs1001179 polymorphism (C262T) was the most extensively studied1112. The CAT C262T polymorphism is encoded on the promoter region, influencing transcriptional and splicing regulation13.…”
mentioning
confidence: 99%
“…Catalase is an important endogenous antioxidant enzyme that detoxifies hydrogen peroxide to oxygen and water, thus limiting the deleterious effects of reactive oxygen species (ROS) (Goyal and Basak, 2010). Therefore, the CAT plays an important role in substance metabolism, the polymorphism of CAT gene was associated with the development of diseases, for instance, systemic lupus erythematosus (Warchol et al, 2008), chronic obstructive pulmonary disease (Taniguchi et al, 2014), invasive cervical cancer (Castaldo et al, 2014), and prostate cancer (Karunasinghe et al, 2012;Tefik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%